Genomic and Clinical Significance of Multiple Primary Lung Cancers as Determined by Next-Generation Sequencing - Goodwin, Daryn; Rathi, Vivek; Conron, Matthew; Wright, Gavin M (Journal of thoracic oncology, 2021)
Marked variations in survival rates have brought into question whether standard clinicopathologic classification should be applied to patients presenting with multiple primary lung cancers (MPLCs). This study investigated the genetic profiles of MPLCs in a cohort of patients using next-generation sequencing and correlated results to clinicopathologic data and patient outcome. Patients treated surgically with curative intent for two putative primaries of similar histopathology from January 2000 to December 2019 at St Vincent's Hospital Melbourne. DNA and RNA was extracted from formalin-fixed, paraffin-embedded tumor tissue and sequenced on an Ion Torrent Personal Genome Machine system. Patient outcome was determined by overall survival and disease-free survival. A total of 40 cases fulfilled the inclusion criteria. Mutational profiling was concordant with clinicopathologic diagnosis in most cases; however, seven cases (17.5%) revealed shared mutations suggesting metastatic disease and this was associated with a substantial reduction in overall survival (p < 0.05). Our results suggest that gene sequencing technologies are potentially a more accurate diagnostic and prognostic tool compared with traditional histopathologic evaluation in patients presenting with suspected MPLCs, which could better guide management and predict outcomes.